Konstruksi Sosial Ideologi Keagamaan dalam Sistem Pertahanan Sosial: Studi Sosiologi Pertahanan di Madura - Chairum Ummah, Kuntum; Raja Dasion, Agustinus Gergorius; Rahmawati, Aminah Dewi (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
This study examines how religious ideology is socially constructed in shaping a social defense system grounded in national defense within the Madurese community. In this context, strong religious values function not only as spiritual guidance but also as the basis for social norms, collective identity, and communal awareness in responding to both military and non-military threats. Using a qualitative approach, this research was conducted in Pamekasan Subdistrict, Madura, East Java, through observation, in-depth interviews, literature review, and Focus Group Discussions (FGDs) involving relevant stakeholders. Data were collected through non-participant observation, genealogical studies, and literature analysis, and were analyzed using qualitative descriptive methods. The study applies the Social Construction of Reality framework, focusing on the processes of externalization, objectification, and internalization. The findings reveal that religious values are continuously produced and reproduced through the roles of kiai, pesantren, and local traditions such as slametan and haul, which have undergone strong institutionalization and become collectively accepted social realities. These values are internalized by individuals, forming a religious habitus that fosters a sense of national defense as a moral and religious obligation. The study concludes that the integration of religious values and national defense generates a cultural and ideological form of social defense that strengthens national resilience from within society. In this context, national defense is understood not only as a physical effort but also as a social practice rooted in spirituality, social solidarity, and collective responsibility. This research contributes to the sociology of defense and offers practical insights for developing national defense awareness programs based on local wisdom and religious values. The role of non-state actors as strategic elements in building social and cultural-based national resilience is the focus of this research